The Eurozone Crisis and the European Union´s Multiple Identity Crises - Ntampoudi, Joanna (2015)
Several commentators of the Eurozone crisis have observed that the UE is not only going through a financial and economic crisis, but also an ´identity crisis´, or even an ´existencial´one. This article argues that the concept of European identity is a multifaceted one that contains numerous dimensions and goes on to explore at least four distinct, yet interrelated ways interpreting the current identity crisis of the EU. The first concerns the international standing of the EU as a proclaimed and exemplary global agent of peace, democracy, welfare and prosperity, which is undermined its inability to provide these goods to its own citizens and close neighbours, let alone the rest of the world. The second kind of identity crisis relates to the EU's qualitative direction in the economic domain, centred on the question of whether we now face a more technocratic and social one. In a third sense, the rise of nationalist sentiments, undiplomatic exchanges between EU citizens based on cultural stereotypes and sharp divides between North and South have contributed to the reconfiguration of perceived prototypical meanings of both national and European identities, undermining their pluralist and gracious visions. Ultimately, all of the above culmitade in the fourth dimension of identity crisis which relates to the internal consistency of the EU wired through the ever-present quest for public support and legitimised through the notions of unity and solidarity. Resumo Vários comentadores da crise da zona do euro observaram que a UE não está apenas a passar por uma crise financeira e económica, mas também uma "crise de identidade", ou mesmo uma "crise existencial". Este artigo argumenta que o conceito de identidade europeia é multifacetado e contém numerosas dimensões e passa a explorar pelo menos quatro formas distintas, porém inter-relacionadas, de interpretar a atual crise de identidade da UE. O primeiro diz respeito à posição internacional da UE como um agente global proclamado e exemplar de paz, democracia, bem-estar e prosperidade, que é prejudicado sua incapacidade de fornecer esses bens a seus próprios cidadãos e vizinhos próximos, assim como ao resto do mundo. O segundo tipo de crise de identidade relaciona-se com a direção qualitativa da UE no domínio económico, centrada na questão de saber se estamos perante uma situação mais tecnocrática e social. Num terceiro sentido, a ascensão de sentimentos nacionalistas, intercâmbios não diplomáticos entre cidadãos da UE baseados em estereótipos culturais e nítidas divisões entre o Norte e o Sul contribuíram para a reconfiguração dos significados prototípicos percebidos das identidades nacionais e europeias, enfraquecendo as suas visões pluralistas e graciosas. Em última análise, a quarta dimensão da crise de identidade relaciona-se com a consistência interna da UE, associada à sempre presente procura por apoio público e legitimada pelas noções de unidade e solidariedade.